2007
DOI: 10.3171/jns-07/10/0821
|View full text |Cite
|
Sign up to set email alerts
|

Axonal supercharging technique using reverse end-to-side neurorrhaphy in peripheral nerve repair: an experimental study in the rat model

Abstract: The reverse end-to-side neurorrhaphy technique could be useful in peripheral nerve repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 22 publications
2
37
0
3
Order By: Relevance
“…To simplify this RETS nomenclature, we prefer the term supercharge end-to-side (SETS) 49 , in a way similar to the vascular description 50 . In 1988, Terzis described this in a clinical report and termed it the babysitter procedure.…”
Section: Discussionmentioning
confidence: 99%
“…To simplify this RETS nomenclature, we prefer the term supercharge end-to-side (SETS) 49 , in a way similar to the vascular description 50 . In 1988, Terzis described this in a clinical report and termed it the babysitter procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of reverse end-to-side nerve suture with axonal supercharging of the recipient nerve has been also experimentally investigated in rat model with complete and incomplete sciatic nerve injuries. These studies demonstrated that functional recovery after peripheral nerve injury was promoted by axonal augmentation [4547]. Nevertheless, to our knowledge, no clinical applications of such technique have been reported up to now.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Th e regenerating axons were augmented and well myelinated by using this technique (Isaacs et al 2005). Additional study showed better sensory and motor functional recovery than with transaction and repair of the right sciatic nerve without augmentation by RETS technique (Fujiwara et al 2007). Th erefore we postulate that coaptation of AIN in RETS fashion provides earlier motor end-plate reinnervation to " babysit " the target muscle and distal nerve stump, as well as augments regenerating axons by the donor and original nerve.…”
Section: Theoretical Fundamental Of the Hypothesismentioning
confidence: 94%